RADICAL CARE AND DECOLONIAL FUTURES: CONVERSATIONS ON IDENTITY, HEALTH, AND SPIRITUALITY WITH INDIGENOUS QUEER, TRANS, AND TWO-SPIRIT YOUTH - Ansloos, Jeffrey; Zantingh, Deanna; Ward, Katelyn; McCormick, Samantha; Bloom Siriwattakanon, Chutchaya (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2021)
The spirituality and health of Indigenous queer, trans, and two-spirit people occurs within and responds to contexts of extreme colonial violence. However, few studies have examined the relationships among the identity, health, and spirituality of Indigenous queer, trans, and two-spirit youth and their perspectives and activism work in relation to the context of this violence. This study aims to better understand the importance of the connections among identity, health, and spirituality and their role in supporting Indigenous queer, trans, and two-spirit leadership in the enactment of care practices to promote health amidst colonial violence and the worlding of decolonial futures beyond and outside it. Informed by key insights from the grassroots movements and fields of Indigenous feminism, Indigenous queer thought, and radical resurgence, this study brings these insights into conversation, via qualitative interviews with five Indigenous youth activists (18 to 35 years old) from across the part of Turtle Island now known as Canada. Our analysis results in four themes: (1) identity, (2) spirituality, (3) the multidimensional nature of colonial violence, and (4) radical care. We delineate activating practices for decolonial futures, and signal the value of grounded, context-reflective, culturally safe, and intersectional health and youth services. This research demonstrates that spirituality is constitutive of and foundational to the identity and health of Indigenous queer, trans, and two-spirit youth, and shows that health promotion and youth services must address the multidimensional nature of these needs if they are to truly support Indigenous young people, their movements of radical care, and the creation of a decolonial elsewhere marked by belonging, love, self-determinism, responsibility, and joy.